2016
DOI: 10.24880/maeuvfd.260790
|View full text |Cite
|
Sign up to set email alerts
|

Anti̇oksi̇danlar

Abstract: ÖZETSon yıllarda en fazla çalışılan konulardan olan serbest radikaller ve antioksidanlar gün geçtikçe daha da önem kazanmaktadır. Normal şartlar altında canlı metabolizması sağlıklı iken antioksidanlar ile serbest radikaller denge halindedir. Ancak bu denge serbest radikaller lehine değiştiği zaman, oksidatif stres kaynaklı hastalıklara yatkınlık gözlenmektedir. Özellikle çevre kirliliği, alkol ve sigara kullanımı, orman yangınları, X-rays ve UV ışınları gibi eksojen serbest radikal kaynaklarının artışı, insan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 43 publications
(51 reference statements)
1
23
0
7
Order By: Relevance
“…It results from peroxidation of multiple saturated fatty acids. CAT, SOD, GSH-Px, and glutathione reductase (GSH-RD) have a vital role in signal transduction, immune response, and proliferation regulation in cells (Karabulut & Gülay, 2016). Previous studies have reported that GSH level decreased in septic shock (Carbonell et al, 2000;Ortolani et al, 2000).…”
Section: Ta B L Ementioning
confidence: 99%
“…It results from peroxidation of multiple saturated fatty acids. CAT, SOD, GSH-Px, and glutathione reductase (GSH-RD) have a vital role in signal transduction, immune response, and proliferation regulation in cells (Karabulut & Gülay, 2016). Previous studies have reported that GSH level decreased in septic shock (Carbonell et al, 2000;Ortolani et al, 2000).…”
Section: Ta B L Ementioning
confidence: 99%
“…Furthermore, it was observed that in the control and antibiotic-treated groups, which did not receive any antioxidant supplement, the level of free radicals increased with higher storage temperature and prolonged storage, and eventually led to increased levels of MDA, as an indicator of peroxidation having occurred. Karabulut and Gülay (2016) indicated that unfavourable environmental conditions increase the generation of free radicals and cause oxidation, and suggested that antioxidant supplementation is required under such circumstances as the available level of antioxidants falls short.…”
Section: Discussionmentioning
confidence: 99%
“…Antioxidants are substances that eliminate the negative effects of free radicals and prevent damage to cells. They are examined in two groups as endogenous and exogenous antioxidants (Karabulut & Gülay, 2016). Endogenous antioxidants are classified as enzymatic or non-enzymatic antioxidants.…”
Section: Antioxidant Effectmentioning
confidence: 99%